Pelatihan Reparasi dan Perawatan Peralatan Elektronik Rumah Tangga untuk Meningkatkan Lifeskills Masyarakat di Kenagarian Kapau Alam Pauh Duo - Doni Tri Putra Yanto; Ahyanuardi Ahyanuardi (Universitas Negeri Padang, 2019)
This study reveals the improvement of people's lifeskills after attending a repair and maintenance program for household electronic equipment in Kenagarian Kapau Alam Pauh Duo, Kecamatan Pauh Duo, Kabupaten Solok Selatan. Lifeskills in question is the ability in the field of repairing and maintaining household electronic equipment that is commonly used in everyday life. Increased ability of trainees is measured by using a research instrument in the form of Performance Assessment Rubric that has been through the validation process. The research data are analyzed by percentage analysis and interpreted with an improvement table to get the level of improvement achieved. Research subjects are 15 trainees who were community representatives in the Nagari Kapau Alam Pauh Duo. The results showed that the average participant experienced an increase in the field of repair and maintenance of household electronic equipment after attending training activities where the increase occurred at very high levels (average total = 83.32). Thus, it can be concluded that the reparation training program and maintenance of household electronic equipment is able to increase the lifeskill of the community in Kenagarian Kapau Alam Pauh Duo in the field of repair and maintenance of household electronic equipment.